ANALISIS MUTU PALM KERNEL PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DI SUMATERA BARAT - Romadhan, Hendro; Alfi, Rizki (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2022)
One of the palm oil processing industries in West Sumatra, in relation to meeting customer demand, experienced internal problems related to kernel quality, where there was inconsistent water and dirt content in the kernel. This can be seen from the analysis data on the water content and seed dirt in April 2021 which did not meet the quality parameter standards based on the Indonesian National Standard (SNI) 01-0002-1987, which is a maximum moisture content of 8%, maximum. dirt content of 6% and maximum broken seeds of 15%. Production analysis is carried out to measure kernel quality in the industry using the Seven Tools method (Histogram and Control Map) to improve the problems faced by the company as well as workplace maintenance to produce improvements and improve the quality of the products produced. The kernel quality level produced meets the standards set by the national standardization body, where the kernel quality level is a water content of 7.60% and an impurity content of 4.58%. In the process capability analysis, the Cp value is 1.11 for water content and 1.10 for dirt content, where a value of 1 < Cp < 1.33 means that the process capability is good, but more control is needed if the Cp value approaches 1.00.